Differences in gene expression between high and low tolerance rainbow trout (Oncorhynchus mykiss) to acute thermal stress. - Leah A Turner; Anne A Easton; Moira M Ferguson; Roy G Danzmann (PLoS ONE)
Understanding the mechanisms that underlie the adaptive response of ectotherms to rising temperatures is key to mitigate the effects of climate change. We assessed the molecular and physiological processes that differentiate between rainbow trout (Oncorhynchus mykiss) with high and low tolerance to acute thermal stress. To achieve our goal, we used a critical thermal maximum trial in two strains of rainbow trout to elicit loss of equilibrium responses to identify high and low tolerance fish. We then compared the hepatic transcriptome profiles of high and low tolerance fish relative to untreated controls common to both strains to uncover patterns of differential gene expression and to gain a broad perspective on the interacting gene pathways and functional processes involved. We observed some of the classic responses to increased temperature (e.g., induction of heat shock proteins) but these responses were not the defining factors that differentiated high and low tolerance fish. Instead, high tolerance fish appeared to suppress growth-related functions, enhance certain autophagy components, better regulate neurodegenerative processes, and enhance stress-related protein synthesis, specifically spliceosomal complex activities, mRNA regulation, and protein processing through post-translational processes, relative to low tolerance fish. In contrast, low tolerance fish had higher transcript diversity and demonstrated elevated developmental, cytoskeletal, and morphogenic, as well as lipid and carbohydrate metabolic processes, relative to high tolerance fish. Our results suggest that high tolerance fish engaged in processes that supported the prevention of further damage by enhancing repair pathways, whereas low tolerance fish were more focused on replacing damaged cells and their structures.